The Effect of Online Lecture on College Students' Learning Achievement During the Covid-19 Pandemic - Khalilah Ramadhani (State Institute of Islamic Studies Imam Bonjol Padang, 2021)
College student learning achievement shows a reflection of mastery of knowledge both in quality and quantity which is influenced by several factors. This study was conducted to determine the influence of lecturers' teaching factors, interactive media, and learning motivation on college student learning achievement during the Covid-19 pandemic. The approach used in the reseach is quantitative with 50 college students from three different universities as reseach subjects. Data were collected through a questionnaire instrument google form by method simple random sampling or randomly selected. Then analyzed using multiple logistic regression analysis technique with the help of SPSS for windows. This study shows the results that the teaching of lecturer has no effect on increasing college student learning achievement, but interactive media and learning motivation have a positive effect on college student learning achievement. This study recommends further research to examine the effect of lecturer competence on online lectures during the Covid-19 pandemic.